Neutron–Proton Scattering Length Data Extracted from the Reaction at MeV - Kasparov, A. A.; Mordovskoy, M. V.; Afonin, A. A.; Mitsuk, V. V. (Physics of atomic nuclei, 2025)
The breakup reaction at an energy of 5 MeV was studied on the RADEX neutron channel of the Institute for Nuclear Research of the Russian Academy of Sciences. As a result of comparing the experimental data with the simulation results, the energy of the virtual state keV and the corresponding singlet scattering length fm were extracted. It was assumed that the obtained value, together with the data of other experiments on the study of and breakup reactions at different energies, are subject to the influence of forces. The work was carried out as part of a series of studies on internucleon interactions at low energies.